Analysis Of The Effect Of Motivation And Knowledge About Capital Market, Return, Risk And Minimum Capital On Interest To Invest In The Indonesia Stock Exchange (Case Study In The Financial Audit Board Of The Republic Of Indonesia) - Hesti Umiyati; Subiyanto Subiyanto; Yuli Noor Kusumawati; Agus Suherman; Kasful Anwar; Indra Kumbara Wedha (International Journal of Business, Economics, and Social Development, 2023)
The purpose of this study was to find out how the influence of motivation, capital market knowledge, return, risk and initial capital on interest in investing in the Indonesia Stock Exchange.The research method uses a quantitative approach using primary data in the form of a survey through a questionnaire instrument, while the analytical method uses multiple regression statistical analysis. The research sample is BPK employees with random sampling technique.Based on the results of this study confirms: 1) Motivation has a positive and significant effect on interest in investing, the results of statistical tests noted that 49.4% of investment interest is influenced by motivation which shows that BPK employee motivation has a positive and significant influence on investment interest; 2) Knowledge of the capital market has a positive effect on investment interest. The results of statistical tests noted that 19.8% of BPK employees' investment interest was influenced by knowledge of the capital market; 3) Knowledge of Return has an effect on investment interest. The results of statistical tests noted that only 9.8% of BPK employees' investment interest was influenced by knowledge of returns; 4) knowledge about risk has a positive effect on investment interest. The results of statistical tests noted that 0.277 or 27.7% of knowledge about risk affects the investment interest of BPK employees; 5) Knowledge of minimum capital has an effect on investment interest. The results of statistical tests noted that 11.3% knowledge of minimum capital affects the investment interest of BPK employees; and 6) Motivation, knowledge of the capital market, stock returns, risk and minimal capital together have an effect on interest in investing in the capital market. The results of statistical tests noted that 76.9% interest in investment is jointly influenced by motivation, knowledge of the capital market, stock returns, risk and minimal capital. Meanwhile, the remaining 23.1% is influenced by external factors other than the five independent variables studied.